Anti-invasive effects of 2,6-bis-(4-hydroxyl-3methoxybenzylidine) cyclohexanone and its molecular targets associated with invadopodia formation in MDA-MB-231 human breast cancer cells - Harun, Siti Nor Aini (2018)
Cancer metastasis is a pathological event occurred in cancer patients where it can colonize the distant organs. In order to metastasize, the tumor cells need to migrate and invade the surrounding tissues. Invadopodia are thought to be specialized actin-rich protrusions formed by the highly invasive cells to degrade the dense meshwork of the extracellular matrix (ECM). This is the initial step employed to drive cancer invasion. Cancer metastasis is deadliest and has affected the survival rate of cancer patients. Current cancer treatment has also produced side effects. Chemotherapy has given rise to the invasion and metastasis while radiotherapy has caused the recurrence of cancer. Identification of compound(s) capable to disrupt the metastasis of cancer especially for hindering the invadopodia formation is important so as to provide anti-metastasis targeted therapy. Curcumin has been demonstrated to produce significant effect as an anti-cancer compound. However, due to its poor bioavailability, some analogues have been formulated. A curcuminoid analogue known as 2,6-bis-(4- hydroxyl-3methoxybenzylidine) cyclohexanone or BHMC has shown good potential in inhibiting inflammation and hyperalgesia. It also possesses antitumor effects on 4T1 murine breast cancer cells in vivo. However, there is still lack of empirical evidence on how BHMC works in preventing human breast cancer invasion. In this study, we pursued to investigate the role of BHMC on MDA-MB-231 breast cancer cells its underlying mechanism of action to prevent breast cancer invasion especially on the formation of invadopodia. Analysis revealed that treatment of BHMC at 12.5 μM and below did not interfere with the proliferation of MDA-MB-231 cells. By using scratch migration assay, transwell migration and invasion assays, we found that BHMC at 12.5 μM reduces the percentage of the migration and invasion of MDA-MB-231 cells. The gelatin degradation assay showed that BHMC reduces the number of cells forming invadopodia. Analysis of the proteins involved in invasion showed that there is significant reduction in the expression of Rho guanine nucleotide exchange factor 7 (β-PIX), matrix metalloproteinase-9 (MMP-9) and membrane type 1-MMP (MT1-MMP) in the present of BHMC treatment at 12.5 μM. It can be postulated that BHMC at 12.5 μM is the optimal concentration to prevent the invasiveness of breast cancer cells.